A preparation method of graft copolymer and its application
During the preparation of ABS resin, a redox initiation system combined with water-soluble and oil-soluble initiator is used, and the third initiator is introduced in the aging stage, the problem of high residual monomer content in the ABS resin is solved, and high conversion rate and good impact performance are achieved.
Patent Information
- Application Number
- CN202410802728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-06-20
AI Technical Summary
In the existing ABS resin preparation methods, the residual monomer content is high, the odor and VOC are also high, which limits its application in food packaging, medical supplies and other fields.
By using a redox initiator system combined with water-soluble and oil-soluble initiator in the presence of a graft matrix, and introducing a third initiator during the aging stage, the residual monomer content is reduced, the monomer conversion rate is improved, and the impact performance is improved.
It effectively reduces the residual monomer content in graft copolymer and ABS resin, improves the monomer conversion rate, and improves the impact performance of ABS resin.
Smart Images

Figure QLYQS_1 
Figure BDA0004903836090000051 
Figure BDA0004903836090000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and more specifically to a preparation method and application of a graft copolymer. Background Art
[0002] ABS resin is a widely used thermoplastic polymer, which is usually obtained by emulsion graft polymerization. However, in this preparation method, the monomers fail to react completely during the polymerization process, resulting in a large amount of residual monomers. The final product has high residual monomers, odor and VOC, which limits its application in food packaging, medical supplies, laboratory equipment, toys and other fields.
[0003] Prior art CN106232648A discloses a method for preparing a thermoplastic molding compound with an optimal residual monomer content. By controlling the mass ratio of the components styrene and acrylonitrile in the monomer feed at the end of the monomer feed time to be lower than the accumulated mass ratio during the entire monomer feed time, oil-soluble styrene monomers are preferentially grafted and polymerized, preventing styrene from accumulating and leaving too much residue, thereby improving the monomer conversion rate and reducing the residual monomer content. However, this method does not reduce the residual monomer content of acrylonitrile monomers with good water solubility, and under the premise of a certain initiator, this method has a limited degree of improving the conversion rate. If the conversion rate is improved by increasing the amount of initiator used, the impact properties of the material will be reduced. Therefore, the present invention provides a method for preparing a graft copolymer and an ABS resin, which have a low total residual monomer content, a high conversion rate and good impact properties. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that low residual monomer content, high conversion rate and impact performance cannot be achieved in the prior art, and to provide a method for preparing a graft copolymer. The total residual monomer content in the prepared graft copolymer is low and the conversion rate is high. The ABS resin prepared by the graft copolymer has good impact performance.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions:
[0006] A method for preparing a graft copolymer comprises the following steps:
[0007] In the presence of a grafting base, styrene monomers and vinyl cyanide monomers are emulsion polymerized and grafted to obtain a graft copolymer;
[0008] The grafting process is divided into a monomer addition reaction stage and an aging stage; in the monomer addition reaction stage, a first initiator and a second initiator are added, the first initiator is an oil-soluble initiator, the second initiator is a water-soluble initiator, the amount of the oil-soluble initiator added is 0.4-0.7wt% of the styrene monomer; the amount of the water-soluble initiator added is 0.1-0.5wt% of the vinyl cyanide monomer; in the grafting process, at least one reducing agent is added to form a redox initiation system with the oil-soluble initiator;
[0009] A high-efficiency initiator is added during the aging stage, and the third initiator is a peroxide containing tert-butyl.
[0010] Preferably, the structure of the third initiator is:
[0011] Wherein X is a phenyl group or an alkyl group, and the number of carbon atoms in the alkyl group is 4 to 12.
[0012] Specifically, the present invention can be realized when the number of carbon atoms in the alkyl group is 4, 5, 6, 7, 8, 9, 10, 11 or 12.
[0013] The preparation method of the present invention forms a redox initiation system by adding a water-soluble initiator and an oil-soluble initiator and coordinating a reduction system. A third initiator is introduced in the aging stage, and the third initiator has a low decomposition temperature and activation energy, which can further reduce the residual monomer content. The thermal initiation and the redox initiation system work together in the aging stage to finally achieve a high conversion rate. The amount of the initiator is controlled to avoid excessive introduction of the initiator to reduce the impact performance, thereby effectively reducing the residual monomer content. The obtained graft copolymer is used to prepare ABS resin with good impact performance.
[0014] Specifically, the third initiator is an oil-soluble initiator.
[0015] Specifically, the self-accelerating decomposition temperature of the peroxide containing tert-butyl group is 20-60° C. By selecting the peroxide containing tert-butyl group at this self-accelerating decomposition temperature, free radicals can be decomposed more efficiently, and the initiation effect can be higher in synergy with thermal initiation.
[0016] Specifically, the self-accelerating decomposition temperature can be determined according to a thermal storage test.
[0017] Preferably, the third initiator is tert-butyl peroxide; more preferably, it is one or more of tert-butyl perbenzoate, tert-butyl perpivalate or tert-butyl perlaurate.
[0018] Preferably, the oil-soluble initiator is added in an amount of 0.5 to 0.65 wt % of the styrene monomer.
[0019] Preferably, the amount of the water-soluble initiator added is 0.2-0.4 wt % of the vinyl cyanide monomer.
[0020] Preferably, the amount of the third initiator added is 0.4-0.8 wt % of the total mass of the styrene monomer and the vinyl cyanide monomer; more preferably 0.5-0.7 wt %.
[0021] Specifically, the total amount of initiator does not exceed 1.4 wt % of the total amount of monomers, and preferably does not exceed 1.2 wt % of the total amount of monomers.
[0022] Specifically, the oil-soluble initiator is a peroxide initiator and / or an azo compound initiator. Preferably, the peroxide initiator is one or more of cumene hydroperoxide, benzoyl peroxide, tert-butyl benzoyl peroxide or dicumyl peroxide; the azo compound initiator is azobisisobutyronitrile and / or azobisisoheptylnitrile.
[0023] Specifically, the water-soluble initiator is a persulfate; preferably, the persulfate is one or more of sodium persulfate, potassium persulfate or ammonium persulfate.
[0024] Preferably, the mass ratio of the graft base to the total mass of the styrene monomer and the vinyl cyanide monomer is 75:25 to 45:55. Preferably, the mass ratio is 70:30 to 40:60; more preferably, the mass ratio is 60:40 to 50:50.
[0025] Specifically, the graft base is a rubber-containing graft base. Preferably, the graft base is polybutadiene latex.
[0026] In a specific embodiment, the average particle size of the graft base is 250 to 350 nm; preferably, the average particle size of the graft base is 280 to 320 nm.
[0027] Preferably, the mass ratio of the styrene monomer to the vinyl cyanide monomer is 60:40 to 90:10, and more preferably, the mass ratio is 70:30 to 80:20.
[0028] Specifically, the styrene monomer is one or more of styrene, α-methylstyrene or C1-C4 alkylstyrene.
[0029] Specifically, the vinyl cyanide monomer is acrylonitrile and / or methacrylonitrile.
[0030] Specifically, the reducing agent is a divalent iron salt, such as but not limited to ferrous sulfate.
[0031] In some specific embodiments, a reducing agent and a complexing agent may be added to form a reducing system.
[0032] Specifically, the auxiliary reducing agent is a carbohydrate substance, such as but not limited to one or more of glucose, lactose, ribose, sorbose, D(+) xylose, cellobiose, and D(+) galactose.
[0033] Specifically, the complexing agent can form a complex with iron ions to control the release of iron ions, such as but not limited to tetrasodium pyrophosphate, sodium diethylamine tetraacetate, and the like.
[0034] Specifically, the total addition amount of the reducing system is 0.5-1.0 wt % of the dry basis of the grafting base.
[0035] In some specific embodiments, a reducing agent and a complexing agent are further added, and the mass ratio of the reducing agent, the reducing agent and the complexing agent can be 1: (50-70): (20-50).
[0036] Specifically, the monomer addition reaction stage comprises the following steps:
[0037] Continuously adding styrene monomers, vinyl cyanide monomers and an initiator dropwise into at least one grafting substrate to sequentially perform a first stage polymerization reaction and a second stage polymerization reaction; or
[0038] Part of the styrene monomer, vinyl cyanide monomer and part of the initiator are added to at least one grafting substrate at one time to carry out a first stage polymerization reaction; then, the remaining styrene monomer, vinyl cyanide monomer and the remaining initiator are continuously added dropwise to carry out a second stage polymerization reaction.
[0039] Specifically, the first stage polymerization reaction is carried out at 70-75°C; and the second stage polymerization reaction is carried out at 75-85°C.
[0040] Specifically, the reaction temperature in the aging stage is 80-90°C.
[0041] Specifically, during the grafting process, auxiliary agents may be added according to the prior art, such as but not limited to emulsifiers, chain transfer agents, and the like.
[0042] Specifically, the amount of the emulsifier added is 0-1 wt % of the dry basis of the graft base, preferably 0.1-0.8 wt %, and more preferably 0.3-0.7 wt %.
[0043] The added amount of the chain transfer agent is 0-0.5 wt % of the dry basis of the graft base, preferably 0.1-0.3 wt %.
[0044] Specifically, the emulsifier is one or more of potassium disproportionate rosin acid, potassium oleate, fatty acid potassium, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.
[0045] Specifically, the chain transfer agent is tert-dodecyl mercaptan and / or n-dodecyl mercaptan.
[0046] In some specific embodiments, the method for preparing the graft copolymer comprises the following steps:
[0047] Method 1:
[0048] a. Add water, part of the emulsifier (e.g., 65-75% of the total amount of the emulsifier), and polybutadiene latex to a graft polymerization reactor, start stirring and heat to 60-65°C, add the reducing system, add part of the styrene monomer (e.g., 15-25% of the total amount of the styrene monomer), part of the vinyl cyanide monomer (e.g., 15-25% of the total amount of the vinyl cyanide monomer) and part of the chain transfer agent (e.g., 30-40% of the total amount of the chain transfer agent) at one time, add part of the initiator (e.g., 30-50% of the total amount of the oil-soluble initiator and the water-soluble initiator), stir the reaction for 50-70 minutes, the stirring speed is 120-180 rpm, and the temperature is raised to 70-75°C, which is the first stage polymerization reaction;
[0049] b. Add the remaining styrene monomer, vinyl cyanide monomer and chain transfer agent mixture, emulsifier and remaining initiator to the product obtained in the first stage polymerization reaction, raise the temperature to 80-85°C, react for 120-180min, and stir at 120-180rpm for the second stage polymerization reaction;
[0050] c. Add a third initiator to the product obtained by the second stage polymerization reaction, raise the temperature to 80 to 90° C., react for 40 to 70 minutes, and cool to obtain a graft copolymer;
[0051] Method 2:
[0052] Add water, polybutadiene latex and reducing system into the graft polymerization reaction kettle, start stirring and heat to 60-65°C, add styrene monomer, vinyl cyanide monomer and chain transfer agent mixed solution, emulsifier and initiator continuously, heat from 60-65°C to 70-75°C within 0-2h and keep for the first stage polymerization reaction, then start heating, heat from 70-75°C to 80-85°C within 2-4h and keep for the second stage polymerization reaction, at this time the monomer feeding is finished, and the initiator and emulsifier feeding is finished after 30min, and the stirring speed is 140-180rpm throughout the whole process;
[0053] A third initiator is added to the product obtained by the above reaction, the temperature is raised to 80-90° C., the reaction is carried out for 40-70 minutes, and the graft copolymer is obtained by cooling.
[0054] The invention also provides a graft copolymer prepared by the above preparation method.
[0055] The invention also provides a graft copolymer high-rubber powder, which is obtained by agglomerating the graft copolymer.
[0056] In a specific embodiment, the method for preparing the graft copolymer high-rubber powder comprises the following steps:
[0057] Add graft copolymer coagulant and desalted water into the gel kettle, stir and heat to 65-80°C, add graft copolymer, add all within 0.5-2h, heat to 90-95°C, maintain for 0.5-2h, coagulate and dehydrate to obtain graft copolymer high-gel powder.
[0058] Specifically, the amount of the coagulant added is 0.1 to 0.5 wt % of the graft copolymer.
[0059] Specifically, the amount of desalted water added is 100-300 wt % of the graft copolymer.
[0060] Specifically, the residual salt content in the desalted water is 1-5 mg / L.
[0061] Specifically, the coagulant is a 3-10wt% magnesium sulfate solution.
[0062] The water content of the graft copolymer high rubber powder is less than 10 wt %, preferably less than 8 wt %; more preferably less than 5 wt %.
[0063] The present invention also provides an ABS resin, wherein the ABS resin comprises the following components calculated in parts by weight:
[0064]
[0065] Specifically, the weight average molecular weight of the styrene-acrylonitrile copolymer is preferably 85,000 to 250,000 g / mol, more preferably 100,000 to 225,000 g / mol.
[0066] Specifically, the weight average molecular weight is determined by GPC (solvent: tetrahydrofuran, polystyrene as polymer standard) according to DIN 55672-1:2016-03 with UV detection.
[0067] In a specific embodiment, the type of polymer component can be selected according to actual needs, and other polymer components include but are not limited to one or more of polycarbonate, polyamide and polyester.
[0068] In a specific embodiment, the other components include, but are not limited to, one or more of fillers, reinforcing agents, colorants, lubricants, release agents, stabilizers, antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides or foaming agents.
[0069] Specifically, the filler or reinforcing agent includes, but is not limited to, one or more of silicate, amorphous silicon dioxide, calcium silicate, quartz, mica, metal oxide, metal hydroxide, graphite, barium sulfate, calcium carbonate, magnesium carbonate, talc, kaolin, carbon fiber or glass fiber.
[0070] Specifically, the colorant includes but is not limited to one or more of titanium dioxide, phthalocyanine, ultramarine, iron oxide or carbon black.
[0071] Specifically, the stabilizer includes but is not limited to one or more of diphenyl ether, salicylate, benzotriazole or benzophenone.
[0072] Specifically, the release agent includes, but is not limited to, fatty acids having 12 to 30 carbon atoms, salts thereof, and derivatives thereof, such as stearic acid, stearate, palmitic acid, palmitate, stearyl alcohol, amide wax, polyolefin wax, and the like.
[0073] In the present invention, commonly used antioxidants can be selected according to the prior art, such as but not limited to one or more of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants.
[0074] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (Irganox 1098), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 259), β-(4-hydroxy-3,5-di-tert-butylphenyl)propionic acid n-octadecyl (Irganox 1076) or 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylate]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane (ADK AO-80).
[0075] Specifically, the phosphite antioxidant is distearyl pentaerythritol diphosphite (618), 2,4-di-tert-butylphenol and / or bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite.
[0076] Specifically, the thioester antioxidant is one or more of distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.
[0077] In the present invention, commonly used lubricants can be selected according to the prior art, such as but not limited to at least one of amide lubricants, stearate lubricants, ester lubricants or silicone lubricants.
[0078] The present invention also provides a method for preparing the above ABS resin, comprising the following steps:
[0079] The above components are mixed evenly and granulated to obtain ABS resin.
[0080] The present invention also protects the use of the above ABS resin in the preparation of automotive interior materials, food packaging, medical supplies, laboratory equipment, and toys.
[0081] Compared with the prior art, the present invention has the following beneficial effects:
[0082] The invention provides a graft copolymer. By mixing a water-soluble initiator and an oil-soluble initiator, combining a reducing agent to form a redox system, combining with a thermal initiation system, and introducing a third initiator in the aging stage, the residual monomer content in the graft copolymer and the ABS resin prepared therefrom can be effectively reduced, the conversion rate is high, and the impact performance of the prepared ABS resin is good. DETAILED DESCRIPTION
[0083] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0084] The raw materials used in the embodiments and comparative examples are:
[0085] Grafting substrate: polybutadiene latex, average particle size 280-320 nm, prepared with reference to CN116554376A latex-1;
[0086] Styrene monomer: styrene, purity greater than or equal to 99%, commercially available;
[0087] Vinyl cyanide monomer: acrylonitrile, purity greater than or equal to 99%, commercially available;
[0088] Styrene-acrylonitrile copolymer, PN-128L100, Chi Mei, Taiwan, China;
[0089] Initiator:
[0090] Water-soluble initiator 1: potassium persulfate, commercially available;
[0091] Water-soluble initiator 2: sodium persulfate, commercially available;
[0092] Oil-soluble initiator 1: cumene hydroperoxide, commercially available;
[0093] Oil-soluble initiator 2: azobisisobutylnitrile, commercially available;
[0094] The third initiator:
[0095] The third initiator 1: tert-butyl peroxybenzoate, with a self-accelerating decomposition temperature of 35°C, commercially available;
[0096] The third initiator 2: tert-butyl peroxylaurate, with a self-accelerating decomposition temperature of 50°C, commercially available;
[0097] The third initiator 3: tert-butyl peroxypivalate, with a self-accelerating decomposition temperature of 20°C, commercially available;
[0098] Emulsifier: potassium oleate, commercially available;
[0099] Chain transfer agent: tert-dodecyl mercaptan, commercially available;
[0100] Reducing agent: ferrous sulfate, commercially available;
[0101] Co-reducing agent: glucose, commercially available;
[0102] Complexing agent: tetrasodium pyrophosphate, commercially available;
[0103] The mass ratio of the reducing agent, the auxiliary reducing agent and the complexing agent in the reduction system is 1:65:30.
[0104] Other components:
[0105] Antioxidant: a mixture of antioxidant 618 and antioxidant 1076 in a mass ratio of 2:1, both of which are commercially available;
[0106] Lubricant: vinyl bisstearamide, commercially available;
[0107] The same commercially available products were used in the parallel experiments of the embodiments of the present invention and the comparative examples.
[0108] Examples 1 to 6 and Comparative Examples 1 to 6
[0109] Examples 1 to 6 and Comparative Examples 1 to 6 provide a graft copolymer, which is prepared by the following method according to the formula in Table 1:
[0110] a. Add water, part of the emulsifier (e.g., 70% of the total amount of the emulsifier), and polybutadiene latex to a graft polymerization reactor, start stirring and heat to 60-65°C, add the reducing system, add part of styrene (e.g., 20% of the total amount of styrene), part of acrylonitrile (e.g., 20% of the total amount of acrylonitrile), and part of the chain transfer agent (e.g., 37.5% of the total amount of the chain transfer agent) at one time, add part of the initiator (e.g., 40% of the total amount of the oil-soluble initiator and the water-soluble initiator), stir and react for 60 minutes, the stirring speed is 160 rpm, and the temperature is raised to 70-75°C during the process, which is the first stage of the polymerization reaction;
[0111] b. Add the remaining styrene, acrylonitrile and chain transfer agent mixture, the remaining emulsifier and the remaining initiator to the product obtained by the first stage polymerization reaction, raise the temperature to 80-85°C, react for 150min, and stir at 160rpm for the second stage polymerization reaction;
[0112] c. Add the third initiator to the product obtained from the second stage polymerization reaction, raise the temperature to 85-90°C, maintain for 60 minutes, and cool to obtain a graft copolymer.
[0113] Table 1 Component dosage in each embodiment and comparative example (unit: weight part)
[0114]
[0115]
[0116] It should be noted that the weight parts of the polybutadiene latex described in the examples are all converted to dry basis weight parts.
[0117] Example 7
[0118] According to the dosage of each component of Example 1 in Table 1, water, polybutadiene latex and reducing system are added to the graft polymerization reaction kettle. When the temperature is raised to 60-65°C by stirring, styrene, acrylonitrile and chain transfer agent mixed solution, emulsifier and initiator are continuously added dropwise, and timing is started. The temperature is raised from 60-65°C to 70-75°C within 0-2h and maintained for the first stage polymerization reaction. Then the temperature is raised from 70-75°C to 80-85°C within 2-4h and maintained for the second stage polymerization reaction. At this time, the monomer feeding is completed, and the initiator and emulsifier feeding are completed after 30min. The stirring speed throughout the process is 160rpm; the third initiator is added to the above reaction product, the temperature is raised to 85-90°C, and maintained for 60min to obtain a graft copolymer.
[0119] Examples 8 to 14 and Comparative Examples 7 to 12
[0120] The graft copolymers in the above-mentioned embodiments and comparative examples were coagulated, and 400 parts of 10 wt% magnesium sulfate solution and 3000 parts of desalted water were added to the coagulation kettle, stirring was started and the temperature was raised to 75° C., and 3000 parts of the graft copolymer were slowly added within 0.5 to 2 hours, and the temperature was raised to 92° C., and the timing was started for 20 minutes. After the coagulation, the slurry was centrifuged, washed with desalted water twice, and dried at 60° C. for 1 hour to obtain a graft copolymer high-rubber powder with a water content of less than 1%;
[0121] The graft copolymer high rubber powder, styrene-acrylonitrile copolymer and auxiliary agents are mixed uniformly according to the amounts in Table 2, and ABS resin is obtained by extrusion granulation.
[0122] Table 2 Amount of ABS resin components used in each embodiment and comparative example (unit: weight parts)
[0123]
[0124]
[0125] Performance Testing
[0126] 1. Graft copolymer performance test:
[0127] (1) Solid content and monomer conversion test:
[0128] Take 1.0±0.05g of the graft copolymer prepared in the examples and comparative examples and spread it evenly in an aluminum dish, then place it horizontally in a blast oven, dry it at 130±5℃ for 30min, take it out and place it in a desiccator to cool it to room temperature, weigh it to the nearest 0.1mg. Then put it back in the blast oven and dry it at 130±5℃ for 10min until the difference between two consecutive weighings is less than 0.5mg. The total solid content is calculated according to the following formula:
[0129] Solid content = (m2-m) / (m1-m)*100%;
[0130] Where, m is the mass of the aluminum dish, g;
[0131] m1 is the mass of the aluminum dish and sample before drying, g;
[0132] m2 is the mass of the aluminum dish and sample after drying, g;
[0133] The conversion rate is calculated based on the solid content. The calculation formula for the monomer conversion rate is as follows:
[0134] Conversion rate = (solid content * total mass of materials added to the polymerization reactor - total mass of non-volatile additives) / total mass of monomers added to the polymerization reactor * 100%.
[0135] (2) Test for residual monomers in graft copolymers
[0136] Using gas chromatography and headspace sampling, the sample is separated by a capillary column and then calibrated by a hydrogen flame ionization detector, and the content of each component is determined by the external standard method.
[0137] The analysis conditions are as follows:
[0138] Headspace injection: HS-10 constant temperature oven 80°C, sample flow path 200°C, transfer line 215°C
[0139] Inlet: temperature 230 °C, split ratio 100:1, injection time 1 min, septum purge flow rate, 3 mL / min.
[0140] Column box: initial temperature 60℃, retention time 4.5min, first-order heating rate 20℃ / min, final temperature 85℃, holding time 3min, second-order heating rate 20℃ / min, final temperature 180℃, holding time 3min
[0141] Front detector FID: temperature 320℃, tail gas N2: 24ml / min.
[0142] Gas pressure and flow rate: APC1 pressure 260.0kPa
[0143] Quantitative method: External standard method
[0144] Standard curve: Acrylonitrile: 20-150mg / L; Styrene: 10-100mg / L
[0145] Specific operations and calculations:
[0146] Weigh 0.1000 g of the sample, accurate to 0.1 mg, into a headspace bottle, add 10 ml of methanol, seal the bottle, place it in an ultrasonic instrument for 5 minutes, and take it out for analysis.
[0147]
[0148] X: Sample content in latex: unit: ppm
[0149] C: Instrument output: unit: mg / L
[0150] m: sample dry basis: unit: g.
[0151] The test results are shown in Table 3.
[0152] Table 3 Graft copolymer experimental data
[0153]
[0154] As can be seen from Table 3, the present invention adopts a mixture of water-soluble initiator and oil-soluble initiator, and combines with the third initiator to significantly improve the monomer conversion rate and significantly reduce the residual monomer content.
[0155] 2. ABS resin performance test
[0156] (1) Izod notched impact test: The above ABS resin was tested according to GB / T 1843-2008 standard;
[0157] (2) Yellowness index: The above ABS resin was tested according to HG / T 3862-2006 standard;
[0158] (3) Residue test in ABS resin
[0159] Using gas chromatography and the headspace method, the sample is separated by a capillary column and then tested by a hydrogen flame ionization detector to determine the content of each component according to the internal standard method;
[0160] The analysis conditions are as follows:
[0161] Headspace injection: HS-10 constant temperature oven 80°C, sample flow path 210°C, transfer line 215°C
[0162] Inlet: temperature 230℃, split ratio 100:1, injection time 1min: septum purge flow rate, 3ml / min. Column box: initial temperature 60℃, retention time 1min, first-order heating rate 5℃ / min, final temperature 80℃, holding time 0min, second-order heating rate 1℃ / min, final temperature 85℃, holding time: 0min. Third-order heating rate 5℃ / min, final temperature 100℃, holding time 0min, fourth-order heating rate 40℃ / min, final temperature 225℃, holding time 5min.
[0163] Front detector FID: temperature 320℃, tail gas N2: 24mL / min.
[0164] Gas pressure and flow rate: APC1 pressure 260.0kPa
[0165] Quantitative method: External standard method
[0166] Specific operations and calculations:
[0167] Weigh 0.25 g of the sample, accurate to 0.1 mg, into a headspace bottle, add 10 ml of o-dichlorobenzene (with internal standard), seal the bottle, place it in an oscillator for 7 hours, and take it out for analysis.
[0168]
[0169] X: Sample content in latex: unit: ppm
[0170] C: Instrument output: unit: mg / Lm: Sample mass: unit: g. The test results are shown in Table 4.
[0171] Table 4 ABS resin experimental data
[0172]
[0173]
[0174] It can be seen from Table 4 that the graft copolymer prepared by the method of the present invention is used to prepare the ABS resin, in which the residual monomer content is low and the material has good impact properties. Specifically, the residual monomer content of acrylonitrile does not exceed 60ppm. The residual monomer content of styrene does not exceed 600ppm, the yellowness index does not exceed 18, and the notched impact performance is not less than 16kJ / m 2 .
[0175] It can be seen from Comparative Examples 1-2 and Comparative Examples 7-8 that when a single initiator is used, even if a reducing agent and a third initiator are added, the conversion rate of the obtained graft copolymer is relatively low, and the residual monomer content is significantly higher than that in the embodiment, and the performance of the ABS resin obtained therefrom deteriorates.
[0176] It can be seen from Comparative Examples 3 and 9 that using other inorganic peroxides to replace the third initiator in the present invention cannot improve the monomer conversion rate well, and the residual monomer content is high. The ABS resin prepared by using the other inorganic peroxides has a high residual monomer content.
[0177] It can be seen from Comparative Examples 4 and 10 that if the reducing system is not added, even if a mixed initiator is used and a third initiator is added, the monomer conversion rate cannot be improved well, and the residual monomer content is high. The ABS resin prepared by using the mixed initiator has a high residual monomer content.
[0178] It can be seen from Comparative Examples 5 and 11 that using other initiators without tert-butyl groups to replace the third initiator in the present invention cannot improve the monomer conversion rate well, and the residual monomer content is high. The ABS resin prepared by using the initiators has a high residual monomer content.
[0179] It can be seen from Comparative Examples 6 and 12 that although increasing the amount of initiator can effectively improve the monomer conversion rate and the residual monomer content, the impact properties of the ABS resin prepared therefrom are significantly reduced.
[0180] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a graft copolymer, characterized in that: The steps include: In the presence of a grafting base, styrene monomers and vinyl cyanide monomers are emulsion polymerized and grafted to obtain a graft copolymer; The grafting process is divided into a monomer addition reaction stage and an aging stage; in the monomer addition reaction stage, a first initiator and a second initiator are added, the first initiator is an oil-soluble initiator, the second initiator is a water-soluble initiator, the amount of the oil-soluble initiator added is 0.4-0.7wt% of the styrene monomer; the amount of the water-soluble initiator added is 0.1-0.5wt% of the vinyl cyanide monomer; in the grafting process, at least one reducing agent is added to form a redox initiation system with the oil-soluble initiator; In the aging stage, a third initiator is added, wherein the third initiator is a peroxide containing a tert-butyl group; and the amount of the third initiator added is 0.4-0.8wt% of the total mass of the styrene monomer and the vinyl cyanide monomer.
2. The method for preparing the graft copolymer according to claim 1, characterized in that: The mass ratio of the graft base to the total mass of the styrene monomer and the vinyl cyanide monomer is 75:25 to 45:
55.
3. The method for preparing the graft copolymer according to claim 1, characterized in that: The structure of the third initiator is: ; Wherein X is a phenyl group or an alkyl group, and the number of carbon atoms in the alkyl group is 4 to 12.
4. The method for preparing the graft copolymer according to claim 1, characterized in that: The third initiator is tert-butyl peroxide.
5. The method for preparing the graft copolymer according to claim 4, characterized in that: The tert-butyl peroxide is one or more of tert-butyl perbenzoate, tert-butyl perpivalate or tert-butyl perlaurate.
6. The method for preparing the graft copolymer according to claim 1, characterized in that: The styrene monomer is one or more of styrene, α-methylstyrene or C1-C4 alkylstyrene; the vinyl cyanide monomer is acrylonitrile and / or methacrylonitrile; and the grafting matrix is polybutadiene latex.
7. The method for preparing the graft copolymer according to claim 1, characterized in that: The oil-soluble initiator is a peroxide initiator and / or an azo compound initiator.
8. The method for preparing the graft copolymer according to claim 7, characterized in that: The peroxide initiator is one or more of cumene hydroperoxide, benzoyl peroxide, tert-butyl benzoyl peroxide or dicumyl peroxide; the azo compound initiator is azobisisobutyronitrile and / or azobisisoheptylnitrile.
9. The method for preparing the graft copolymer according to claim 1, characterized in that: The water-soluble initiator is persulfate.
10. The method for preparing the graft copolymer according to claim 9, characterized in that: The persulfate is one or more of sodium persulfate, potassium persulfate or ammonium persulfate.
11. The method for preparing the graft copolymer according to claim 1, characterized in that: The mass ratio of the styrene monomer to the vinyl cyanide monomer is 60:40 to 90:
10.
12. The method for preparing the graft copolymer according to claim 1, characterized in that: The monomer addition reaction stage comprises the following steps: Continuously adding styrene monomers, vinyl cyanide monomers and an initiator dropwise into at least one grafting substrate to carry out a first stage polymerization reaction and a second stage polymerization reaction; or Part of the styrene monomer, vinyl cyanide monomer and part of the initiator are added to at least one grafting substrate at one time to carry out a first stage polymerization reaction; then, the remaining styrene monomer, vinyl cyanide monomer and the remaining initiator are continuously added dropwise to carry out a second stage polymerization reaction.
13. A graft copolymer, characterized in that: The method is prepared by any one of claims 1 to 12.
14. A graft copolymer high-rubber powder, characterized in that: The graft copolymer according to claim 13 is used for coagulation to obtain the product.
15. An ABS resin, characterized in that: The ABS resin includes the following components calculated by weight: 13-35 parts of the graft copolymer high-rubber powder according to claim 14; Styrene-acrylonitrile copolymer 65-85 parts.
16. A method for preparing the ABS resin according to claim 15, comprising the following steps: The above components are mixed evenly and granulated to obtain ABS resin.
17. Use of the ABS resin according to claim 15 in the preparation of automotive interior materials, food packaging, medical supplies, laboratory equipment, and toys.
Citation Information
Patent Citations
Thermoplastic molding compounds with an optimized residual monomer content
CN106232648A
Polybutadiene latex and preparation method thereof, ABS high rubber powder and preparation method and application thereof
CN116554376A
ABS resin and preparation method thereof
CN111171239A
High-heat-resistance ABS (acrylonitrile-butadiene-styrene) resin and preparation method thereof
CN116375945A